Otto Neurath and the legacy of ISOTYPE - Lima, Ricardo Cunha (InfoDesign, 2025)
The work of Otto Neurath (1882-1945) and his team, through ISOTYPE (International System of TYpographic Picture Education) deeply influenced information design. In this article I attempt do describe the course of events that led Neurath to create ISOTYPE, and then analyze the legacy of ISOTYPE in pictograms and infographics in journalism. This legacy was not limited to Europe and USA and this is shown through examples of the influence of ISOTYPE in Brazil.